THE EDUCATOR'S ETHICAL COMPASS APPROACH: A MORAL NAVIGATOR IN DEVELOPING STUDENTS' EMOTIONAL-SPIRITUAL QUOTIENT - Mohammad Usman (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to analyze the role of teachers as moral navigators through an ethical compass approach in fostering students' emotional spiritual quotient (ESQ). The research method used was descriptive qualitative with a case study type. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation studies. Data analysis applied the Miles and Huberman model which included data reduction, data presentation, and drawing conclusions, while data validity was guaranteed through source and technical triangulation techniques. The findings indicated that ESQ development is carried out through three integrative steps: Modeling (exemplary calibration) which provided visual logic based on integrity and sirah; Coaching (emotional navigation) which honed empathy and self-control (EQ); and Meaning Making (activation of spiritual meaning) which connected actions with transcendental values (SQ). The implementation of these three steps successfully transformed student motivation from mere compliance with rules to inner awareness, which is manifested in concrete actions such as charity, infaq, and sincere social concern. The implications of this study emphasized that the success of character education was highly dependent on the teacher's capacity to align intellectual, emotional, and spiritual aspects simultaneously. Teachers no longer played the role of mere material instructors, but rather as a life compass that guided students to have strong internal moral navigation amidst the dynamics of the times.